Can closeness, conflict, and dependency be used to characterize students' perceptions of the affective relationship with their teacher? Testing a new child measure in middle childhood. (26th September 2015) - Koomen, Helma M. Y.; Jellesma, Francine C.
Abstract : Background: The constructs of closeness, conflict, and dependency, which are derived from attachment theory, are widely used to qualify teachers' perceptions of relationships with individual children. Aims: Our main aim was to reveal whether similar and reliable dimensions could be identified in middle childhood with a newly developed student measure Student Perception of Affective Relationship with Teacher Scale (SPARTS). Additional validity support was sought by examining gender differences and associations with (1) teacher relationship perceptions and (2) problem and prosocial behaviours in children. Sample(s): Factor structure was determined in a sample of 586 children (46.5% boys) from 26 regular elementary Dutch classrooms (grade 4–6). Associations with teacher relationship reports ( n  = 82) and child behaviours ( n  = 64) were analysed in random subsamples. Methods: Students' relationship perceptions were assessed with the SPARTS; teachers' relationship perceptions with the Student–Teacher Relationship Scale (STRS; closeness, conflict, and dependency); and problem and prosocial behaviours in children with the teacher‐reported Strengths and Difficulties Questionnaire. Results: Exploratory factor analysis and confirmatory factor analysis supported a 3‐factor model of conflict, closeness, and a third factor, unexpectedly reflecting negative expectations of the student instead of dependency. Satisfactory internal consistency was found for all three scales. Additional validity evidence included the following: Substantial student–teacher agreement for conflict and closeness; meaningful associations with problem and prosocial behaviours in children; and expected gender differences showing that, compared to boys, girls share more favourable relationships (more closeness and less conflict) with teachers. Conclusions: The 3‐dimensional SPARTS comes close to the attachment‐derived teacher STRS, as far as conflict and closeness are concerned. The third dimension, negative expectations, represents a new and relevant attachment‐related dimension reflecting a lack of confidence of students in the relationship with their teacher.